The Challenges of E-government Implementation in Developing Countries - Arini Ansyelika Pangaribuan (JPAS (Journal of Public Administration Studies), 2019)
E-government has great potential to improve the way government works in order to provide public services and increase stakeholder involvement in public services. However, there are still many challenges in implementing e-government in many developing countries around the world. The purpose of this literature review is to summarize the challenges of e-government implementation in developing countries. The result show that e-government implementation in developing countries faced complex problems as following lack of ICT infrastructure, lack of security and privacy of information, lack of proper planning, public awareness, cultural resistance, institutional and political, and lack of budgeting. Therefore, in order to get benefit from e-government implementation, the government needs to overcome these challenges.